Efektivitas Layanan Bimbingan Kelompok Dengan Teknik Diskusi Untuk Meningkatkan Kemampuan Perencanaan Karir Siswa SMA Minqotrotul Ulum Gumukmas Jemer - Umi Lailatul Magfiroh; ST. Fanatus Syamsiyah; Wahid Suharmawan (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
This research aims to describe the effectiveness of discussion techniques in improving the career planning of Minqotrotul Ulum Jember High School students. This type of research is One Group Pre-test Post-test Design. The sample in this study consisted of 52 students, 10 students who had a low level of career planning. The data collection technique in this research uses a questionnaire. The results obtained in this study show that the level of career planning increased after being given treatment in the form of group counseling using discussion techniques. This can be seen from the results of the pretest and posttest of the study, in the pretest showed a low score of career planning level and the posttest showed the results of the score of career planning level increased, so the conclusion is that after being given treatment the level of career planning of students increased, in the sense that the Discussion method is effective to improve the career planning skills of high school students Minqotrotul Ulum Jember.